A multiple criteria approach to two-stage data envelopment analysis. (July 2016) - Mahdiloo, Mahdi; Jafarzadeh, Abdol Hossein; Saen, Reza Farzipoor; Tatham, Peter; Fisher, Ron
Highlights: A new approach for evaluating and ranking sustainable suppliers. A two-stage DEA approach for multiple criteria sustainable processes analysis. Model provides improved discrimination power to traditional two-stage DEA models. More effective sustainability assessment of the DMUs is achieved using the model. Abstract: Two-stage data envelopment analysis (DEA) models are commonly used in the evaluation and benchmarking of sustainable operations and processes across multiple research fields. To date, however, little attention has been given to the unrealistic weight distribution and weak discrimination power in the modeling and evaluation of the two-stage sustainable operations when using two-stage DEA models. In order to overcome this methodological weakness, we use the multiple criteria DEA (MCDEA) approach in the evaluation of the two-stage processes. The outcome is a multiple criteria two-stage DEA model which yields more realistic weights for the inputs and outputs and thus has better discrimination power than traditional two-stage DEA models. The developed model is tested and validated by assessing the sustainable design performances of a sample of car product designs.